Experimental study of the effects of hypoxia simulator on osteointegration of titanium prosthesis in osteoporotic rats - Jiangfeng Liu (BMC, 2021)
Abstract Background Poor osseointegration is the key reason for implant failure after arthroplasty,whether under osteoporotic or normal bone conditions. To date, osseointegration remains a major challenge. Recent studies have shown that deferoxamine (DFO) can accelerate osteogenesis by activating the hypoxia signaling pathway. The purpose of this study was to test the following hypothesis: after knee replacement, intra-articular injection of DFO will promote osteogenesis and osseointegration with a 3D printed titanium prosthesis in the bones of osteoporotic rats. Materials and methods Ninety female Sprague–Dawley rats were used for the experiment. Ten rats were used to confirm the successful establishment of the osteoporosis model: five rats in the sham operation group and five rats in the ovariectomy group. After ovariectomy and knee arthroplasty were performed, the remaining 80 rats were randomly divided into DFO and control groups (n = 40 per group). The two groups were treated by intraarticular injection of DFO and saline respectively. After 2 weeks, polymerase chain reaction (PCR) and immunohistochemistry were used to evaluate the levels of HIF-1a, VEGF, and CD31. HIF-1a and VEGF have been shown to promote angiogenesis and bone regeneration, and CD31 is an important marker of angiogenesis. After 12 weeks, the specimens were examined by micro-computed tomography (micro-CT), biomechanics, and histopathology to evaluate osteogenesis and osseointegration. Results The results of PCR showed that the mRNA levels of VEGF and CD31 in the DFO group were significantly higher than those in the control group. The immunohistochemistry results indicated that positive cell expression of HIF-1a, VEGF, and CD31 in the DFO group was also higher. Compared with the control group, the micro-CT parameters of BMD, BV/TV, TB. N, and TB. Th were significantly higher. The maximal pull-out force and the bone-to-implant contact value were also higher. Conclusions The local administration of DFO, which is used to activate the HIF-1a signaling pathway, can promote osteogenesis and osseointegration with a prosthesis in osteoporotic bone.